Art of the Story in the Classical and Modern Arabic Literature - Shamsud, Professor Dr Salahuddin Bin Mohd; Binti Hj. Ahmad, Siti Sara (IJRDO- Journal of Educational Research, 2018)
The story appeared in the prose later than the poetic epic and drama in the world literature. The story was the last literary genre that had emerged in the world literatures. It was free from the restrictions of the literary criticism and least committed to the rules of criticism. This freedom made it to take urgent steps towards the progress in the modern age, overtaking the other genres in the performance of the humanitarian message of the literature. Therefore, it obtained a superiority and a social and artistic status among the other literary genres in the grand literatures. There were some narrative elements in the ancient epic that helped the emergence of narrative prose in Greek literature in the second century AD for the first time. The story had the nature of epic at that time, which was included the metaphysical adventures, magic and supernatural things. The events of story in that era were running around the separation of couple, horrific dangers, frightening scenes and obstacles that were counted as a reason of the separation between them, but they crossed all those obstacles by some unusual ways. Then there was an happy ending by the meeting held between them. In this article we study six stories entitled: “One Thousand and One Night”, “Disciples and Cyclones”, “Message of Forgiveness”, “Message of Ḥayyi b. Yaqdhān” and Story of Salāmān and Absāl. There are some religious stories of prophets mentioned in Quran, but the art of technical story was not intended by them.